Globally standardized MODIS spectral mixture models. Issue 10 (3rd October 2019) - Sousa, Daniel; Small, Christopher
ABSTRACT: Standardized substrate, vegetation, and dark (S, V, & D) spectral endmembers (EMs) are presented for spectral mixture analysis (SMA) of MODIS version 6 daily nadir looking BRDF-adjusted reflectance (daily NBAR). EMs are derived from a diverse collection of over 43, 000, 000MODIS spectra spanning 6 continents and all non-polar biomes. EM spectra are similar to those from decametre studies. Sensitivity analysis using 351 pairs of 27 EM combinations shows mean differences in SVD fraction estimates of 4±3%, 3±2%, and 3±2%, respectively. An additional snow EM is identified, but deemed tentative pending further cryospheric analysis. Vicarious validation with Landsat shows under 0.5% bias in V fraction, −7% and +11% biases in S and D fractions, and comparable dispersion (standard deviation 6% to 7%) in all fractions. Model misfit is low (root-mean-square error under 5% for 99.9% pixels). When V is compared to Normalized Difference, Enhanced, and Soil Adjusted Vegetation Indices (NDVI, EVI, SAVI), NDVI shows over twice the dispersion (standard deviation 29% vs 13–14%) and over 4 times the bias (+18% vs 4%) of EVI and SAVI. Combined with previous studies, these results extend the scaling linearity and low misfit of the global SVD linear mixture model from 2m up to 500m.